The Effectiveness of Electronic Medical Records by Nurses at Hospitals in East Kalimantan - Ratanto Ratanto; Rizky Setiadi; Arifin Hidayat (Borneo Scientific Publishing, 2026)
The implementation of electronic medical records (EMRs) has increased significantly in hospitals worldwide, including in Indonesia, due to their potential to improve healthcare quality, enhance efficiency, reduce medical errors, and support clinical decision-making. However, the effectiveness of EMR implementation varies across healthcare settings, highlighting the need for systematic evaluation. This study aimed to assess the effectiveness of EMR implementation in hospitals in East Kalimantan, Indonesia. A quasi-experimental study with a two-group post-test-only design was conducted involving 188 participants from two hospitals. Data were collected simultaneously and analyzed using the Mann–Whitney U test with a significance level of 0.05. The results revealed significant differences between the two hospitals in the dimensions of quality (p = 0.001), facilities (p = 0.028), functionality (p = 0.017), user satisfaction (p = 0.003), and overall effectiveness (p = 0.014). Hospitals implementing EMRs demonstrated higher effectiveness scores compared with hospitals that had not implemented EMRs. In conclusion, EMR implementation significantly influences the effectiveness of medical record management. These findings highlight the importance of optimizing EMR systems to improve healthcare service quality and operational performance in hospitals.